Fabrication of ultra-high-temperature nonstoichiometric hafnium carbonitride via combustion synthesis and spark plasma sintering. Issue 10 (July 2020) - Buinevich, V.S.; Nepapushev, A.A.; Moskovskikh, D.O.; Trusov, G.V.; Kuskov, K.V.; Vadchenko, S.G.; Rogachev, A.S.; Mukasyan, A.S.
Abstract: In this study, nonstoichiometric hafnium carbonitrides (HfC x N y ) were fabricated via short-term (5 min) high-energy ball milling of Hf and C powders, followed by combustion of mechanically induced Hf/C composite particles in a nitrogen atmosphere (0.8 MPa). The obtained HfC0.5 N0.35 powder exhibited a rock-salt crystal structure with a lattice parameter of 0.4606 nm. The melting point of this synthesized ceramic material was experimentally shown to be higher than that of binary hafnium carbide (HfC). The nonstoichiometric hafnium carbonitride was then consolidated under a constant pressure of 50 MPa at a temperature of 2000 °C and a dwelling time of 10 min, through spark plasma sintering. The obtained bulk ceramic material had a theoretical material density of 98%, Vickers hardness of 21.3 GPa, and fracture toughness of 4.7 MPa m 1/2 .